Airborne sound insulation performance of lightweight double leaf walls with different stud types - Hequn Min; Bo Wang; Ting Qu (Scientific Reports)
Abstract Lightweight double leaf walls have been extensively employed in assembly and large-space buildings. Due to the complex and varied stud configurations in double leaf walls, accurately and efficiently predicting the sound transmission loss (STL) of such structures poses a significant challenge. To support performance-based design workflows, this paper presents an analytical model based on sound transmission path decoupling, enabling architects to quickly predict the STL of commonly used lightweight double leaf wall types, including wooden, steel, and acoustical stud constructions. The paper systematically discusses the impact of different stud configurations on sound insulation performance and reveals the underlying mechanisms of sound bridge effects. Results show that the sound bridge effect arises from the structural sound transmission path introduced by various types of studs in the wall, and optimizing stud configurations is essential for decoupling the two leaves of the wall acoustically. Traditional wooden studs, considered as rigid frames, contribute more to the sound bridge effect compared to steel studs of the same structure. A promising approach involving acoustical studs with rubber sound isolation inserts is proposed, which achieves high-level sound insulation performance while offering significant spatial and construction efficiency advantages. This study provides valuable insights into advancing high-performance, lightweight building partitions and contributes to enhancing indoor soundscapes.